Ag2S2O8 meets AgSO4: the second example of metal–ligand redox isomerism among inorganic systems12. Issue 45 (31st October 2016) - Gilewski, Tomasz E.; Leszczyński, Piotr J.; Budzianowski, Armand; Mazej, Zoran; Grzelak, Adam; Jaroń, Tomasz; Grochala, Wojciech
Abstract : Ag(i )2 S2 O8 – prepared here for the first time – constitutes a redox isomer of the already known Ag(ii )SO4 . These "electromers" have identical chemical composition but they differ in all important physicochemical properties. Abstract : Valence (redox) isomerism based on electron exchange between a metal and a ligand is immensely rare in purely inorganic systems, with only one documented case, that of PbS2 which adopts two polymorphic forms corresponding to Pb(iv )(S 2− )2 and Pb(ii )(S2 2− ). Here we have taken advantage of metathetic reactions using salts of weakly coordinating anions and we have prepared for the first time Ag(i )2 S2 O8, silver(i ) peroxydisulphate. The title compound crystallizes in the non-centrosymmetric Cc space group with partial disorder of the anionic sublattice. Ag(i )2 S2 O8 is a highly thermally unstable diamagnetic and colourless valence isomer of the antiferromagnetic and black Ag(ii )SO4, described by us in the past.